2021
DOI: 10.21203/rs.3.rs-100256/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

High copy number variations, particular transcription factors, and low immunity contribute to the stemness of prostate cancer cells.

Abstract: Background: Tumor metastasis is the main cause of death of cancer patients, and the existence of cancer stem cells is the basis of tumor metastasis. However, the systematic analysis of the stemness of prostate cancer cells is still not abundant. This article explores the effective factors that lead to the stemness of prostate cancer cells with multi-omics data mining.Methods: Gene expression modules that were strongly related to the stemness of prostate cancer cells were obtained with WGCNA and stemness scores… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 66 publications
0
3
0
Order By: Relevance
“…It is widely accepted that replication stress plays a key role in initiating anti-tumor immunity by inducing cancerrelated neoantigens (31, 32), and its absence is intensively correlated with the immune desert phenotype. Consequently, the low immunity and high level of CNV can jointly contribute to strong cancer stemness (33), accounting for the result that patients of CS3 were tolerant of many ATR and week1 inhibitors in our study.…”
Section: Discussionmentioning
confidence: 61%
“…It is widely accepted that replication stress plays a key role in initiating anti-tumor immunity by inducing cancerrelated neoantigens (31, 32), and its absence is intensively correlated with the immune desert phenotype. Consequently, the low immunity and high level of CNV can jointly contribute to strong cancer stemness (33), accounting for the result that patients of CS3 were tolerant of many ATR and week1 inhibitors in our study.…”
Section: Discussionmentioning
confidence: 61%
“…For example, in lung adenocarcinoma, CD44, a marker of CSCs, is positively associated with immune cell in ltration (29). M1 macrophages have been reported to play a key role in the development of prostate cancer and the low immune microenvironment is one of the factors leading to the stemness of prostate cancer cells (30). Tumor heterogeneity is one of the main causes of treatment failure.…”
Section: Discussionmentioning
confidence: 99%
“…In the study of Zhang et al, M0 macrophages and M2 macrophages showed a signi cant correlation with prognosis [32] . The top 5 differentiallyexpressed transcription factors, EGR1, SP1, SP4, POU2F1 and NFIC, all showed the potenial in immunotherapy [33][34][35][36][37] . It is worth mentioning that EGR1 is involved in the polarization of macrophages M2 induced by programmed death ligand 1 (PD-L1) to produce anti-PD-L1 treatment resistance and the promotion of metastasis by regulate angiogenic and osteoclastogenic factors [38,39] .…”
Section: Discussionmentioning
confidence: 99%